Fundamental and clinical studies of pazufloxacin in respiratory tract infections - Nishioka, Kiyo; Shirato, Kunio; Tanno, Yasuo (Japanese Journal of Chemotherapy, 1995)
Pazufloxacin (PZFX), a newly synthesized pyridoncarboxylic acid antibacterial agent, was administered to 6 patients with chronic bronchitis, 4 with bronchiectasis, 3 with acute bronchitis, 1 with a secondary infection of diffuse panbronchiolitis and 1 with a secondary infection of pulmonary emphysema, at a single dose of 100 mg or 200 mg twice or three times daily for 6-15 days. The results were excellent in 2, good in 8, fair in 3 and poor in 2, with a total efficacy rate of 66.7%. Among the causative organisms isolated, i.e., 3 strains of Streptococcus pneumoniae, 3 strains of Moraxella catarrhalis and 1 strain of Pasteurella multocida, 2 strains of S. pneumoniae, 3 strains of M catarrhalis and 1 strain of P. multocida were eradicated, with an eradication rate of 6/7. Neither side effects nor abnormal laboratory findings were observed in any subjects. The antimicrobial activity of PZFX against S. pneumoniae, M catarrhalis, Haemophilus influenzae and Pseudomonas aeruginosa, isolated from respiratory tract infections in our department recent years, was compared with that of tosufloxacin (TFLX), ciprofloxacin (CPFX) and ofloxacin (OFLX)[excluding S. pneumoniae in OFLX]. PZFX showed equal or superior antimicrobial activity against M. catarrhalis, H. influenzae and P. aeruginosa, compared with control drugs.